Genetic association and computational analysis of CYP2R1 gene polymorphisms rs2060793 and rs12794714 with vitamin D deficiency and acute myocardial infarction in the Bangladeshi population: A case control study - Sadia Akter; Md. Nazid Bin Ibrahim; Zimam Mahmud; Sonia Tamanna; Md. Shakhawat Hossain Shawon; Farzana Ansari; Md. Zakir Hossain Howlader (PLoS ONE, 2026)
Acute myocardial infarction (AMI) remains a leading cause of cardiovascular morbidity and mortality worldwide. Emerging evidence highlights vitamin D as a critical determinant of cardiovascular health. The CYP2R1 gene encodes the key 25-hydroxylase enzyme responsible for converting vitamin D to its principal circulating metabolite, 25-hydroxyvitamin D. However, the influence of CYP2R1 polymorphisms on AMI susceptibility, particularly within South Asian populations, has not been well characterized. This study investigates the association of two CYP2R1 variants, rs2060793 and rs12794714, with AMI risk and their relationship with serum vitamin D levels in a Bangladeshi cohort. A total of 502 participants comprising 251 AMI patients and 251 age- and sex-matched controls were analyzed. Genomic DNA was extracted and genotyped using PCR-RFLP, while serum 25-hydroxyvitamin D 3 levels were quantified by HPLC. AMI patients exhibited markedly lower vitamin D concentrations (23.92 ± 0.94 ng/mL) than controls (30.3 ± 0.86 ng/mL; p < 0.0001). Genotypic analysis revealed a significant association between rs2060793 and AMI risk: the TC (OR = 2.49, 95% CI: 1.34–4.63) and CC (OR = 2.59, 95% CI: 1.37–4.90) genotypes conferred increased susceptibility compared to the TT genotype ( p = 0.0064). The dominant model (TC + CC vs. TT) further confirmed this relationship (OR = 2.53, 95% CI: 1.39–4.61, p = 0.0016). In contrast, rs12794714 showed no significant association with AMI in this population. Stratified analysis indicated that rs2060793 was significantly linked to AMI in males but not females, while both variants were associated with increased risk in individuals aged ≤60 years, but not in those >60 years. Bioinformatic and molecular docking analyses (RegulomeDB, JASPAR, HADDOCK 2.4, DNAproDB) further demonstrated potential regulatory effects of these variants on CYP2R1 function. Collectively, our findings reveal a novel association between CYP2R1 rs2060793 and vitamin D deficiency with AMI risk in the Bangladeshi population, underscoring the interplay of genetic and metabolic determinants in the molecular pathogenesis of AMI.